Swedish electoral data: Referendum 1980 - Statistics Sweden (Statistics Sweden, 1999)
Election returns for all municipals in Sweden. Includes information on the total number of persons entitled to vote in the referendum, and separately the number of immigrants who have not become citizens of Sweden, but were entitled to vote in this referendum, number of persons who actually voted, number of persons who voted for the different alternative, number of blank votes, and number of valid and invalid ballots.

Valresultat för samtliga kommuner i Sverige för folkomröstningarna i kärnkraftsfrågan 1980 och EU-medlemskapet 1994. Innehåller bland annat uppgifter om total andel röstberättigade i folkomröstningarna, antal icke svenska medborgare som var röstberättigade i folkomröstningarna, valdeltagande, antal personer som röstade för olika alternativ, antal blanka röster samt andel giltiga och ogiltiga röster.
Svenska valdata: Folkomröstningen 1980
Keywords: elections; val; european union; europeiska unionen; european integration; europeisk integration; nuclear energy; kärnkraft; energy policy; energipolitik; election data; valdata; referendums; folkomröstningar; Energy and natural resources; Energi och naturresurser; Elections; Val; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap